Investors Awareness on Mutual Funds in Bengaluru City – An Empirical Study - Dr. Banda Rajani, Dr. Komati Durga Prasad (International Journal of Advanced Science and Technology, 2019)
In this study, it is discussed about the investor’s awareness on mutual funds in Bengaluru. It is difficult to selective group the investors in a sample as such the population of Bengaluru city is large in number. Compared to earlier days the investment options are changing from risk free to riskier investments. The analyses also show that compared to earlier days the growth of investments in the stock market increased to significant level compared to other conventional investments which are of lesser risks and lower returns. The inexperience of investors about mutual fund coupled with aggressive selling by promising higher returns to the investors have resulted into loss of investors’ confidence due to inability to provide higher return. This requires the Asset Management Companies (AMCs) to comprehend the reserve/conspire determination/changing conduct of the speculators to structure appropriate items to meet the changing budgetary needs of the financial specialists. With this foundation a study was directed among 128 Mutual Fund Investors in Bengaluru to study the factors influencing the fund/scheme selection by the Investors. For analyzing the difference in awareness of mutual funds done through SPSS, Z-Test and One-way ANOVA analysis has been made. Hence, this study is made to evaluate the investor’s awareness on mutual funds’